Trends and risk factors for mortality in elderly burns patients: A retrospective review. Issue 6 (September 2019) - Harats, Moti; Ofir, Hagit; Segalovich, Matan; Visentin, Denis; Givon, Adi; Peleg, Kobi; Kornhaber, Rachel; Cleary, Michelle; Haik, Josef
Highlights: The elderly experience higher mortality rates and poorer outcomes compared to younger burn survivors. Impaired vision and decreased coordination places the elderly at risk of a burn. Consideration of factors affecting mortality is required for comprehensive care in elderly burn patients. Abstract: Introduction: The elderly experience higher mortality rates and poorer outcomes compared to younger burn survivors with similar injuries. Methods: This epidemiological study reviewed records of all admitted elderly burn patients collected from five burns facilities in Israel between 1997–2016. Collected data was limited to the population aged 20+, focused on the population aged 60+. Results: Mortality rates for elderly patients increased with TBSA and increases with age. Regression analyses demonstrated a decrease in mortality of 2.9% (p = 0.013) per 5 years, an overall decrease of 11.6% over the 20-year study period, with the decline more significant for older age groups. This decrease in mortality was much larger than that observed for all burns patients over this period. The most common cause of injury in the elderly population was fire, with mortality rate highest for this cause. There was no effect of gender on mortality rate. Mortality increased when smoke inhalation was present for TBSA<20%, with mortality unaffected by the presence of smoke inhalation for higher TBSA. The need for surgery correlates with high mortality rates. Conclusion: This study identified key factors that impact mortality and demonstrated a large decrease in mortality in the elderly patients over the study period.